Digitizing The Investment Sector in Algeria: a Path to Governance "The Investor's Digital Platform as a Sample" - Berrabah, Mounir; Mahdi, Ridda (Journal of Legal Studies and Researches, 2024)
Digitization is considered one of the most important modern means of sector governance because of the transparency in management it achieves. This highlights the importance of applying digitization in the field of a sensitive sector such as the investment sector. The Algerian legislator, aware of this issue, has sought to digitize this sector, which is shown to us through the investor platform.